Strategi Penerapan Restrukturisasi Pembiayaan Mikro Syariah terhadap Dampak pandemi Covid-19 (Studi Kasus: Bank X) - Lydia Rosintan Simanjutak; Azizah Wayulinaini; Raden Ajeng Entaresmen (STES Islamic Village, 2022)
Problem formulation: 1). How to apply the restructuring of sharia microfinance to the impact of the Covid-19 pandemic (Case Study: Bank X); 2). What is the strategy in terms of strengths, weaknesses, opportunities and threats in implementing the restructuring of sharia microfinance against the impact of the COVID-19 pandemic (Case Study: Bank X). Research objectives: 1). To find out the implementation of sharia microfinance restructuring on the impact of the covid 19 pandemic (case study: Bank X); 2). To find out the strategy on the strengths, weaknesses, opportunities and threats in the implementation of the restructuring of sharia microfinance against the impact of the covid-19 pandemic (Case study: Bank X). The method used in this research is descriptive qualitative using SWOT analysis. The results of this study indicate that the implementation of the sharia microfinance restructuring mechanism at Bank X, (1) the customer submits / makes a letter of application for installment relief / installments, (2) the bank makes a proposal as a reference containing income before the COVID-19 pandemic and after the occurrence of the COVID-19 pandemic. the covid-19 pandemic, (3) the bank submits a proposal to the head office, (4) if it is approved by the head office, the service office bank makes a new contract. Strengths, weaknesses, opportunities and threats in the implementation of sharia microfinance restructuring, namely: (1) strengths, namely; support economic growth stimulus; manage financial performance; managing liquidity and capital; and provide opportunities for business actors; (2) weaknesses namely; occurrence of default; not all customers can restructure; and the bank's income is very small; (3) opportunities namely; digitization and customer survival; (4) threats namely; decreased customer business; and manipulate income reports.